Preparation, X-ray Structure, and Reactivity of Triisopropylsilyl-Substituted Aryliodonium Salts; European Journal of Organic Chemistry; Vol. 2015, iss. 22 - Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Svitich D. Yu. Dmitry Yurjevich; Yoshimura A. Akira; Kaster B. J. Brent; Nemykin V. N. Viktor Nikolaevich; Zhdankin V. V. Viktor Vladimirovich (2015, 2015)
Title screen